The generalizability of working-memory capacity in the sport domain. (August 2017) - Buszard, Tim; Masters, Rich SW; Farrow, Damian
Highlights: Working-memory (WM) capacity has been associated with sport-related skills. The generalizability of findings from controlled experiments is unknown. There is no evidence that sport experts possess a larger WM capacity. Research should explore the WM capacity of particular types of players in sport. Focus should be geared towards causal relationships rather than only correlations. Abstract : Working-memory capacity has been implicated as an influential variable when performing and learning sport-related skills. In this review, we critically evaluate evidence linking working-memory capacity with performing under pressure, tactical decision making, motor skill acquisition, and sport expertise. Laboratory experiments link low working-memory capacity with poorer performance under pressure and poorer decision making when required to inhibit distractions or resolve conflict. However, the generalizability of these findings remains unknown. While working-memory capacity is associated with the acquisition of simple motor skills, there is no such evidence from the available data for complex motor skills. Likewise, currently there is no evidence to suggest that a larger working-memory capacity facilitates the attainment of sport expertise.